Globalisation, Tax Competition and the Harmonisation of Corporate Tax Rates in Europe: A Case of Killing the Patient to Cure the Disease? - K. Mccarthy; F. van Doorn; Brigitte Unger (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
This paper surveys the literature on tax competition, and uses it to analyse current European proposals to harmonise corporate tax rates. It begins, in the course of Section One, by introducing the phenomenon of international tax competition, and illustrates, with the use of secondary research, the reality of the regulatory 'race to the bottom'. Section Two, however, demonstrates the harmful consequences of tax competition – with reference to the immobile factors of production – and makes obvious the necessity of effective intervention. Section Three then introduces and evaluates the calibre of the current proposals to tackle tax competition through collusion and harmonisation, and concludes negatively in the process. As illustrated in this discussion, any efforts to harmonise corporate taxes above the international equilibrium will not only fail to solve the problem at hand, but will exacerbate them, and may even serve to undermine and destabilise the political Union. Section Four then introduce an alternative solution to the problem – in the form of the residence principle – and Section Five concludes.
Keywords: 330; International Competition; Europe; Public Finance; Taxation; Regulation